Broadening the scope of task shifting in the organisation of healthcare. (September 2021) - van Tuyl, Lilian; Vrijhoef, Bert; Laurant, Miranda; de Bont, Antoinette; Batenburg, Ronald
Task shifting in healthcare has mainly been initiated and studied as a way to react to/or mitigate workforce shortages. Here, we define task shifting as the structural redistribution of tasks, usually including responsibilities and competencies between different professions. As such, task shifting is commonly focused on highly specialised and trained professionals who hand-over specific, standardised tasks to professionals with lower levels of education. It is expected that this type of task shifting will lead to efficiency and cost savings to healthcare organisations. Yet, there are more benefits to task shifting, in particular its contribution to integrated patient-centred quality of care and a tailored system that meets the changing care demands in society. Hence the importance to broaden the scope of task shifting, its goals, manifestations and how task shifting plays a role in addressing both the strengths and weaknesses in the healthcare system. In this focus piece, trends and conditions for task shifting and its (un)anticipated effects are discussed. We argue that, only when designed to face specific complexities at the workplace and taking into account the balance between specialists and generalists, task shifting may substantially contribute to enhanced quality of care that meets the changing needs of society.